MacroH2A histone variants limit chromatin plasticity through two distinct mechanisms - Kozłowski, Marek; Scheffzek, Klaus (EMBO reports, 2018)
MacroH2A histone variants suppress tumor progression and act as epigenetic barriers to induced pluripotency. How they impart their influence on chromatin plasticity is not well understood. Here, we analyze how the different domains of macroH2A proteins contribute to chromatin structure and dynamics.
Gesehen am 30.01.2020